Ethnic meat products of the North-African and Mediterranean countries: an overview - (:unkn) unknown (My University, 2018)
Traditional meat products constitute one of the ancient cultural heritages of the North African and Mediterranean countries: Egypt, Libya, Tunisia, Algeria, and Morocco. Over years, people of these countries consumed numerous meat products in such a way that biochemical and microbial actions can take place not only to help increase the shelf life but also to enhance the flavor and nutritional quality of the products. These ethnic meat products are prepared using different animal sources, but all verified to be halal, and consumed during local events, family celebrations, or religious feasts. In this systematic review, 32 most known traditional meat products (melfouf, merguez, kofta, guedid, cured guedid, El messli, kourdass, tidkit, soudjouk/sucuk/nakanek, boubnita, pastirma, fregate, merdouma/mandi/bourdim, tafra-gara, maynama, khliaa ezir, laknaf, osbana, bnadek, khlii, kobiba, mcharmla, boubnita/membar, mkila, tehal/tehane, ban-chems, bouzelouf/zelif, klaya, douara/bekbouka/T'qalia, tangia, mrouzia, and cachir) from the five countries were documented. The main objectives of this overview were to report the traditional knowledge that covers the origin, preparation, characteristics, and consumption habits of the 32 North African traditional meat products. Moreover, the listed meat products were grouped into five categories using both traditional and scientific knowledge related to their preparation. The identified categories are (i) salted and/or marinated meat products but not dried (Category I); (ii) dried not fermented meat products (Category II); (iii) fermented semidry/dried meat products (Category III); (iv) smoked meat products (Category IV), and (v) cooked and/or candied meat products (Category V). The common eating practices of these products and the related historical and sociocultural aspects were discussed.
Keywords: African Research